Laboratory Evaluation of Fatigue and Rutting Performance of Nano CaCO3 Modified Asphalt Binders - Amir Mohammad Yarahmadi; Gholamali Shafabakhsh; Adel Asakereh (Journal of Rehabilitation in Civil Engineering)
Evaluating the efficacy of Nano CaCO3 particles on amelioration of fatigue and rutting behavior of asphalt binder is the principal aim of this article. To this end, asphalt binder specimens are fabricated by incorporating various amounts of Nano CaCO3 (0.3%, 0.6%, 0.9%, and 1.2%) with asphalt binder 60-70. Fatigue and rutting performance of the asphalt binder specimens are examined by implementing linear amplitude sweep and multiple stress creep recovery experiments. Results indicated that incorporating Nano CaCO3 with the asphalt binder specimens enhanced their resistance to rutting. Asphalt binder samples containing Nano CaCO3 showed higher potential for compensating the induced strains than unmodified samples. Also, by adding Nano CaCO3, the asphalt binder specimens showed improved fatigue behavior. Asphalt binder samples modified with Nano CaCO3 exhibited better behavior when subjected to cyclic loads than unmodified ones. Also in all cases, the asphalt binder specimens containing 0.9% Nano CaCO3 demonstrated the best performance.